Extracellular vesicles from Listeria monocytogenes-infected dendritic cells alert the innate immune response - Izquierdo-Serrano, Raúl; Fernández-Delgado, Irene; Moreno-Gonzalo, Olga; Martín-Gayo, Enrique; Calzada-Fraile, Diego; Ramírez-Huesca, Marta; Jorge, Inmaculada; Camafeita, Emilio; Abián, Joaquín; Vicente-Manzanares, Miguel; Veiga, Esteban; Vázquez, Jesús; et al. (Frontiers in Immunology, 2022)
Communication through cell-cell contacts and extracellular vesicles (EVs) enables immune cells to coordinate their responses against diverse types of pathogens. The function exerted by EVs in this context depends on the proteins and nucleic acids loaded into EVs, which elicit specific responses involved in the resolution of infection. Several mechanisms control protein and nucleic acid loading into EVs; in this regard, acetylation has been described as a mechanism of cellular retention during protein sorting to exosomes. HDAC6 is a deacetylase involved in the control of cytoskeleton trafficking, organelle polarity and cell migration, defense against Listeria monocytogenes (Lm) infection and other immune related functions. Here, we show that the protein content of dendritic cells (DCs) and their secreted EVs (DEVs) vary during Lm infection, is enriched in proteins related to antiviral functions compared to non-infected cells and depends on HDAC6 expression. Analyses of the posttranslational modifications revealed an alteration of the acetylation and ubiquitination profiles upon Lm infection both in DC lysates and DEVs. Functionally, EVs derived from infected DCs upregulate anti-pathogenic genes (e.g. inflammatory cytokines) in recipient immature DCs, which translated into protection from subsequent infection with vaccinia virus. Interestingly, absence of Listeriolysin O in Lm prevents DEVs from inducing this anti-viral state. In summary, these data underscore a new mechanism of communication between bacteria-infected DC during infection as they alert neighboring, uninfected DCs to promote antiviral responses.